Protective effects of l-carnitine upon toxicopathological alterations induced by ochratoxin A in white Leghorn cockerels. (1st October 2016) - Abidin, Zain ul; Khan, Muhammad Zargham; Khatoon, Aisha; Saleemi, Muhammad Kashif; Khan, Ahrar
Abstract: This study was designed to investigate the protective effects ofl -carnitine (LC) against ochratoxin A (OTA) induced toxicopathological alterations in white Leghorn cockerels. Parameters studied included behavioral parameters, mortality, feed intake, body weight gain, relative organ weights and histopathological alterations. Results suggested that OTA induced suppression in behavioral parameters, feed intake, body weight gain, relative organ weights and histopathological alterations were progressively improved when LC was given with 1 mg/kg OTA; however, this protection subsided when 2 mg/kg OTA was given with it. The optimum level of LC required to produce such mitigation at higher OTA levels is yet to be determined; however, the level used in this study is quite sufficient enough to ameliorate toxicopathological alterations induced by OTA up to 1 mg/kg feed.